Respostas

  • Usuário do Brainly
2014-06-26T21:44:44-03:00
A) 2x + 6 = 12

2x + 6 = 12
2x = 12 - 6
2x = 6
x = 6/2
x = 3

B) (6/4)x = 12

(6/4)x = 12
x = 12/(6/4)
x = 12 . 4/6
x = 48/6
x = 8

C) 3x - 15 = 6

3x - 15 = 6
3x = 6 + 15
3x = 21
x = 21/3
x = 7

D) - 3 - 2x = 9 + 4x

- 3 - 2x = 9 + 4x
- 2x - 4x = 9 + 3
- 6x = 12 . (- 1)
6x = - 12
x = - 12/6
x = - 2
2014-06-26T21:46:28-03:00
 2x+6=12      2x=12-6   2x=6      x=6/2   x=3

  
6x=12   6x= 12.4     6x= 48     x= 48/6      x=8 
  4
    3x-15=6    3x= 6+15    3x=21   x = 21/3     x= 7
 
  -3-2x=9+4x          -2x - 4x = 9+ 3     -6x= 12     x= 12/-6   x= -2